Bugging Foucault: Review of Janice Neri, The Insect and the Image: Visualizing Nature in Early Modern Europe, 1500-1700 - Kelleher, Hillary (Humanimalia, 2015)
Janice Neri. The Insect and the Image: Visualizing Nature in Early Modern Europe, 1500–1700. Minneapolis: University of Minnesota Press, 2011. xxvii + 233 pp. 82.50 hc, 27.50 pb.